Penelitian pengaruh penggunaan riklim politilen terhadap sifat ketahanan pukul dan kekerasan - Supraptiningsih Supraptiningsih; Sofyan karani (Majalah Kulit, Karet, dan Plastik, 1989)
The aim of this research is to know further about the influence ot polyethylene reclaim to the characteristic of impact resistance and high density polyethylene (HDPE) compound.The research is done by making HDPE compound with the addition of polyethylene reclaim with various procentage of quantity.In fact the addition on of HDPE reclaim into pure HDPE doesn’t influence the hardness of the compound produced, but it influence the impact resistance to signification phase P 0,05 by linear aquation Y = 10,26 + 0,0887.The compound hardness is approximately 63,2 – 64,0 shore D, and impact resistance is approximately 10,83 – 18,91 kgcm/cm in various variation.